Pengaruh Kepemimpinan, Disiplin Kerja dan Motivasi terhadap Kinerja Aparatur Sipil Negara pada Kantor Dinas Kesehatan Kabupaten Konawe - Bindarto Bindarto (Jurnal Ilmiah Dikdaya, 2022)
This study aims to determine the effect of work discipline, leadership style, and motivation on employee performance at the Konawe District Health Office. The population in this study amounted to 38 people, and the sample in this study was taken as many as 38 respondents. This study uses multiple linear regression analysis using the F-test and t-test with SPSS Version 16.0. Based on the results of the research conducted, it can be concluded that leadership style has a positive and significant effect on employee performance at the Konawe District Health Office, the Work Environment has a positive and significant impact on the performance of Civil Servants at the Konawe District Social Service Office, Organizational Climate has a positive and significant effect on performance. Employees at the Konawe District Health Office.